1981
DOI: 10.1176/ajp.138.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral characteristics of high- and low-IQ autistic children

Abstract: The authors are developing the Behavior Observation Scale to objectively differentiate autistic, normal, and mentally retarded children aged 30--60 months. They describe operational definitions and procedures and report data on the frequency of selected behaviors among 114 children. Prior studies have revealed that to assess the clinical significance of behaviors in autistic children, both frequency of occurrence per subject and the number of children exhibiting the behaviors must be considered concurrently. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(5 citation statements)
references
References 6 publications
2
2
0
1
Order By: Relevance
“…Perhaps the essential element of CI is the limited range of focus, interest, or activity , and is not confounded by the verbal capabilities of the individual. This may allow us to identify CI in a broad range of cases; this is consistent with previous research that has shown that circumscribed interests can be found in higher- and lower-functioning individuals with autism (Bartak & Rutter, 1976; Freeman et al, 1981). …”
Section: Discussionsupporting
confidence: 88%
“…Perhaps the essential element of CI is the limited range of focus, interest, or activity , and is not confounded by the verbal capabilities of the individual. This may allow us to identify CI in a broad range of cases; this is consistent with previous research that has shown that circumscribed interests can be found in higher- and lower-functioning individuals with autism (Bartak & Rutter, 1976; Freeman et al, 1981). …”
Section: Discussionsupporting
confidence: 88%
“…This finding, when added to similar observations of older subjects and matched controls [2327], does not suggest, however, a qualitatively different set of behaviors. Bodfish et al [8] assessed the occurrence of specific topographies of repetitive behaviors as well as their severity in individuals with intellectual disability with and without autism.…”
Section: Phenomenology Of Repetitive Behaviorsupporting
confidence: 46%
“…CIs have been described from the earliest characterizations of autism [2] exist across all levels of symptom severity and intellectual functioning [3] [4] [5] and are ubiquitous in the disorder– an estimated 88% of individuals with an Autism Spectrum Disorder (ASD) experience CIs [6]. While this evidence suggests that CIs constitute an especially pervasive and prevalent clinical characteristic of the autism phenotype, there remains a paucity of empirical research in this area relative to other features of the disorder [7].…”
Section: Introductionmentioning
confidence: 99%